2000
DOI: 10.1111/j.1469-7793.2000.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin‐6 mediates the febrile response to localised inflammation in rats

Abstract: 1 Interleukin (IL)‐6 is an important mediator of the host response to disease and has been proposed, largely based upon circumstantial evidence, as the principal endogenous circulating pyrogen responsible for activating CNS mechanisms in fever during infection and inflammation. In the present investigation, we studied the role of peripheral IL‐6 in fever and its relationship with IL‐1, itself an important endogenous pyrogen and a potent stimulus of IL‐6 production. 2 Injection of lipopolysaccharide (LPS) into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
161
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(172 citation statements)
references
References 50 publications
(90 reference statements)
6
161
2
3
Order By: Relevance
“…Previous work has suggested that the LPS recognition molecule Toll like receptor 4 (TLR4) on immune cells plays a critical role at the onset of the initial phase of fever, and that the later phases of fever are dependent in a redundant way on TLR4 on both hematopoietic and non-hematopoietic cells (Steiner et al, 2006). While those finding seem to indicate that signaling molecules, such as cytokines, released from immune cells initiates fever, they are in disagreement with the finding that the initiation of the febrile response elicited by intravenously administrated LPS precedes the appearance of IL-6 and other cytokines in the blood stream (Cartmell et al, 2000;Givalois et al, 1994;Roth et al, 1993). …”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Previous work has suggested that the LPS recognition molecule Toll like receptor 4 (TLR4) on immune cells plays a critical role at the onset of the initial phase of fever, and that the later phases of fever are dependent in a redundant way on TLR4 on both hematopoietic and non-hematopoietic cells (Steiner et al, 2006). While those finding seem to indicate that signaling molecules, such as cytokines, released from immune cells initiates fever, they are in disagreement with the finding that the initiation of the febrile response elicited by intravenously administrated LPS precedes the appearance of IL-6 and other cytokines in the blood stream (Cartmell et al, 2000;Givalois et al, 1994;Roth et al, 1993). …”
Section: Discussionmentioning
confidence: 94%
“…A large amount of evidence identifies IL-6 as a necessary factor for the fever response even though IL-6 by itself is not or only weakly or moderately pyrogenic (Cao et al, 2001;Cartmell et al, 2000;Chai et al, 1996;Harden et al, 2008;Kozak et al, 1998;LeMay et al, 1990;Lenczowski et al, 1999;Nilsberth et al, 2009a;Rummel et al, 2006). However, the origin of IL-6 in immune-induced fever has not been fully identified, although there are reports showing that IL-6 can be produced by a variety of cells in response to different pathological stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations